Challenges and Opportunities in HRM Research in the Era of Globalization: A Bibliometric Analysis of the Effects of Cultural Diversity and Innovation in Organizations - Muktamar, Ahmad; Wahdiniawati, Siti Annisa; Fatmawati, Fatmawati; Mardikawati, Budi (Westscience Press, 2023)
This bibliometric analysis explores the landscape of Human Resource Management (HRM) research in the context of globalization, cultural diversity, and innovation within organizations. Leveraging a comprehensive dataset comprising influential works, co-authorship patterns, and keyword frequencies, the study aims to uncover the prevailing themes, emerging trends, and collaborative networks in contemporary HRM literature. The analysis encompasses a broad spectrum of topics, ranging from diversity and globalization to sustainability and training. Key findings reveal an overarching emphasis on diversity and globalization, indicating a heightened awareness of the challenges and opportunities associated with managing diverse workforces in the globalized business environment. The study also identifies trends such as the evolving importance of sustainability and the recognition of training as a vital aspect of HRM practices. Co-authorship networks and influential works spotlight the collaborative nature of HRM research and the seminal contributions that have shaped the field. The findings contribute to a nuanced understanding of HRM's role in navigating the complexities of the globalized organizational landscape, shedding light on both the enduring themes and the evolving priorities in HRM scholarship.